EBS generalized severe is an inflammatory disease. (1st February 2019) - Castela, E.; Tulic, M.K.; Rozières, A.; Bourrat, E.; Nicolas, J.‐F.; Kanitakis, J.; Vabres, P.; Bessis, D.; Mazereeuw, J.; Morice‐Picard, F.; Baty, D.; Berard, F.; et al.
Summary: Epidermolysis bullosa (EB) is a group of genetic disorders in which the skin is abnormally fragile. In EB simplex, the skin cells tend to fall apart because their internal scaffolding of keratin fibres is defective, due to mutations in the genes encoding keratins type 5 or 14 (KRT5 and KRT14). But people with the generalised, severe type of EB simplex (EBS‐GS) are sometimes more ill than would be expected just from a mechanical problem with the skin; some even die in infancy, usually from infection. This group from France and Scotland explored the possibility that EBS‐GS patients also have a faulty immune system. They re‐examined skin specimens taken previously for diagnostic purposes from 17 patients with EBS‐GS and also tested fresh skin biopsies and blister fluid from a further 10 patients. They consistently found more inflammatory cells and higher levels of chemicals which promote inflammation (cytokines) than normal. The findings were the same regardless of whether the sample was from blistered or normal‐looking skin and whether the fault was in KRT5 or KRT14. Markers for the cytokine Th17 were particularly high, encouraging them to treat three EBS‐GS patients with the anti‐Th17 drug Apremilast as used in psoriasis. All three reported a dramatic reduction in blisters within the first month, which lasted throughout treatment for up to 10 months, with minimal side‐effects. One patient stopped the Apremilast after 7 months because of nausea and the blistering came back 2 days later. This appears to be a promising new approach to treating EBS‐GS.